2003
DOI: 10.1021/la026716k
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Water with Self-Assembled Monolayers:  Neutron Reflectivity Measurements of the Water Density in the Interface Region

Abstract: We applied neutron reflectivity measurements to hydrophilic and hydrophobic self-assembled monolayers (SAMs) to probe water density at these interfaces. The measurements were motivated by a previous theoretical study which reported a reduced water density at a hydrophobic surface (Lum, K.; Chandler, D.; Weeks, J. D. J. Phy s. Chem. B 1999, 103, 4570) and by our own computer simulations on the hydration force and water density between two methoxy tri(ethylene glycol) terminated undecylthiolate SAMs adsorbed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
214
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(245 citation statements)
references
References 39 publications
25
214
1
5
Order By: Relevance
“…Neutron [547] and X-ray [548] reflectivity experiments confirmed the observed reduced density of water at the interface, while experiments with an ellipsometer excluded nanobubbles on silanated silica [549]. There is now strong evidence, that bridging bubbles contribute to the long-range hydrophobic attraction in many experiments [495] but the whole hypothesis and the effect of nanobubbles are still being debated [550].…”
Section: Hydrophobic Attractionmentioning
confidence: 83%
“…Neutron [547] and X-ray [548] reflectivity experiments confirmed the observed reduced density of water at the interface, while experiments with an ellipsometer excluded nanobubbles on silanated silica [549]. There is now strong evidence, that bridging bubbles contribute to the long-range hydrophobic attraction in many experiments [495] but the whole hypothesis and the effect of nanobubbles are still being debated [550].…”
Section: Hydrophobic Attractionmentioning
confidence: 83%
“…10%; the layer thickness is, however, less than 1.5 nm. Other neutron reflectivity work (Schwendel et al 2003) shows a depletion layer of ca. 2 nm, but one with such a density deficit as to be unphysical.…”
Section: Water In Different Environmentsmentioning
confidence: 98%
“…Early neutron reflectivity studies [31][32][33] of hydrocarbon-water interfaces reported gap widths larger than 10Å, while later x-ray reflectivity measurements on similar systems reported gap widths of less than 5Å. 35, 36 Yet other X-ray 30 and neutron 34 studies reported that there is no gap.…”
Section: Introductionmentioning
confidence: 97%
“…In reality, although the water-hydrophobic interface has been studied by a number of groups, [30][31][32][33][34][35][36][37] the results are inconsistent and have not led to a consensus. Early neutron reflectivity studies [31][32][33] of hydrocarbon-water interfaces reported gap widths larger than 10Å, while later x-ray reflectivity measurements on similar systems reported gap widths of less than 5Å.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation